Performance Analysis of Disc Mill Type FFC-15 Grinder for Making Charcoal Husk Flour - Siskandar, Ridwan; Kusumah, Billi Rifa; Astuti, Lusia Cipto (The University of Lampung, 2024)
This study is motivated by the great potential of rice husk as a waste material that has not yet been optimally utilized. The focus of this research is to evaluate the performance of the FFC-15 disc mill machine in producing flour from rice husk charcoal at three different moisture contents. The variations in the moisture content of rice husk charcoal studied were 10%, 15%, and 20%, with the goal of determining the optimal conditions in the production process of rice husk charcoal flour. The methodology used is experimental with repeated testing to produce data on machine capacity, electrical power consumption, flour yield, flour quality (moisture content, ash content, and mineral content), and the physical parameters of the charcoal. The results show that moisture content significantly affects the milling efficiency and quality of the flour produced, with optimal conditions achieved at a moisture content of 10%. Adjusting the moisture content before the milling process can enhance the operational efficiency of the machine and the quality of the final product. These findings are expected to provide benefits for follow-up by a group or industry that wants to optimize the utilization of rice husk charcoal. Keywords: Disc mill FFC-15, Flour quality, Husk charcoal, Milling efficiency, Moisture content.